Organocatalytic asymmetric Michael addition reaction of aldehydes with 2-furanones: experimental, applications and DFT studies. Issue 6 (14th February 2023) - You, Xiao; Zhu, Wenning; Du, Jiacheng; Liu, Yuehua; Chen, Fumin; Chai, Yongshuai; Zhang, Qiang; Pang, Jingxiang; Liu, Aiqin; Bai, Zhushuang
Abstract : Organocatalytic asymmetric Michael additions of aldehydes to 2-furanones are successfully conducted and have been applied to the synthesis of vorapaxar's analogues. Abstract : Organocatalytic asymmetric Michael addition of aldehydes to 2-furanones are successfully conducted. This study provides an efficient approach to produce highly functionalized chiral γ-lactones, with three consecutive stereogenic carbons accompanied by good yields (up to 89%) and high stereoselectivities (up to 9.2 : 1 dr and 99% ee), which have been applied to the synthesis of vorapaxar's analogues. The results of mechanistic studies using DFT explained the high stereoselectivity. The protonation of anionic malonate with water by a hydrogen bond bridge is the rate-determining step to obtain the main product.